INTERACTIVE VIDEO-BASED LEARNING MODULE DESIGN FOR DIGESTIVE SYSTEM MATERIAL AT SMPN 2 CIMAHI, CIMAHI CITY, WEST JAVA PROVINCE - Dadang Supriyatna; Durahman (CV JK Riset Publishing Group, 2025)
This study aims to design and develop an interactive video-based learning module for the digestive system material taught in Grade VIII at SMPN 2 Cimahi, West Java Province. The research is motivated by the limited effectiveness of conventional teaching methods and the low level of student engagement in grasping abstract biological concepts. Employing a Research and Development (R&D) approach, the study adopts the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. The needs analysis revealed that the majority of students struggled with understanding digestive processes and strongly preferred visual-interactive media. The design and development phases produced a comprehensive module integrating 3D animations, virtual simulations, interactive quizzes, and augmented reality features to foster meaningful learning. Limited trials demonstrated significant improvement in students' learning outcomes, with an average normalized gain score of 0.64 and high engagement levels. Expert and practitioner validation indicated an excellent degree of feasibility across academic, technical, and practical dimensions. The resulting educational module proves to be an effective and innovative tool, well-aligned with the cognitive characteristics of junior high school students and the pedagogical demands of the digital age.